The “load balancing” and “adaptive task completion” algorithms implementation on a pharmaceutical sorting conveyor line - Ihor Nevliudov; Vladyslav Yevsieiev; Svitlana Maksymova; Oleksandr Klymenko (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of the article is advantages and disadvantages of using the "load balancing" and "adaptive task execution" algorithms on the pharmaceutical sorting conveyor. The goal of the work is to analyze the Load Balancing (LB) and Adaptive Task Completion (ATC) sorting algorithms application on pharmaceutical sorting conveyor lines. And also, to consider their advantages and disadvantages in the context of optimizing sorting processes for pharmaceutical products. The following tasks were solved in the article: analysis of the latest research and publications on the research topic; study of the specifics of the application of algorithms for sorting pharmaceutical products on conveyor lines to balance the load on sorting robots; analysis of the Load Balancing (LB) algorithm from the point of view of its application for load balancing on conveyor lines with sorting robots in the field of pharmaceuticals; development of the Load Balancing algorithm for load balancing on conveyor lines with sorting robots in the pharmaceutical field; analysis of the Adaptive Task Completion (ATC) algorithm from the point of view of its application for load balancing on conveyor lines with sorting robots in the field of pharmaceuticals; development of a general Adaptive Task Completion (ATC) algorithm for load balancing on conveyor lines with sorting robots in the pharmaceutical field; highlighting the advantages and disadvantages of the specified algorithms. The following methods were used: simulation modeling methods. The following results were obtained – the advantages and disadvantages of Load Balancing and Adaptive Task Completion algorithms for load balancing on conveyor lines with sorting robots in the pharmaceutical field are formulated; recommendations are given, in which situations, under which conditions, which algorithm should be used. Conclusions. In the context of the pharmaceutical industry, where not only speed but also sorting accuracy is important, Adaptive Task Completion may be a better choice because it takes into account different criteria and dynamically responds to changing conditions. On the other hand, Load Balancing can be effective in environments where sorting speed is paramount, and tasks are homogeneous.